Medical paleomicrobiology: problems and prospects - Goncharov, A. E.; Kolodzhieva, V. V. (Antibiotiki i himioterapiâ, 2021)
The study of microbial DNA from paleontological and archaeological samples is a powerful tool for estimating the molecular evolution of human pathogens. The paper is a retrospective review of the most significant achievements in medical paleomicrobiology. The subject of the discussion is the genetic diversity of ancient microbiomes including pathogenicity and antibiotic resistance genes. Paleomicrobiological studies of permafrost as a repository of pathogenic microbiota are highly promising.